2011
DOI: 10.1099/vir.0.027789-0
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of the genome sequence of guinea pig cytomegalovirus

Abstract: Congenital infection by human cytomegalovirus (HCMV) is a major cause of birth defects and developmental abnormalities. Since guinea pig cytomegalovirus (GPCMV) crosses the placenta and causes infection in utero, GPCMV models are useful for studies of the mechanisms of transplacental transmission. During our characterization of a genomic locus required for GPCMV dissemination in animals, we found that the nucleotide sequence in and around the nearby immediate-early genes in our lineage of GPCMV strain 22122 [d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
45
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 44 publications
1
45
0
Order By: Relevance
“…The new ORFs Rh00.2, Rh94.1, Rh96.1, Rh228.1, and Rh231 are predicted for both RhCMV strains, whereas ORFs Rh163.1, Rh165.1, and Rh166.1 are conserved between RhCMV 68-1 and the ULb= region of the low-passage-number isolate RhCMV CNPRC as described previously (51). However, the total number of ORFs predicted by this method for either RhCMV strain was substantially higher than that for any other published CMV genome (HCMV [25], CCMV [19], mouse CMV [MCMV] [60], rat CMV [RCMV] [76], and guinea pig CMV [GPCMV] [37,67]). Moreover, this annotation predicted that eight ORFs were unique to RhCMV 68-1 (Rh09, Rh39, Rh61, Rh93, Rh94, Rh142.4, Rh153, and Rh220.1) and that four ORFs were unique to RhCMV 180.92 (Rh13.1, Rh106.1, Rh142.3, and Rh178.2).…”
Section: Resultsmentioning
confidence: 89%
“…The new ORFs Rh00.2, Rh94.1, Rh96.1, Rh228.1, and Rh231 are predicted for both RhCMV strains, whereas ORFs Rh163.1, Rh165.1, and Rh166.1 are conserved between RhCMV 68-1 and the ULb= region of the low-passage-number isolate RhCMV CNPRC as described previously (51). However, the total number of ORFs predicted by this method for either RhCMV strain was substantially higher than that for any other published CMV genome (HCMV [25], CCMV [19], mouse CMV [MCMV] [60], rat CMV [RCMV] [76], and guinea pig CMV [GPCMV] [37,67]). Moreover, this annotation predicted that eight ORFs were unique to RhCMV 68-1 (Rh09, Rh39, Rh61, Rh93, Rh94, Rh142.4, Rh153, and Rh220.1) and that four ORFs were unique to RhCMV 180.92 (Rh13.1, Rh106.1, Rh142.3, and Rh178.2).…”
Section: Resultsmentioning
confidence: 89%
“…The UL116 gene is not conserved among alpha and gamma herpesviruses; thus, it does not belong to the core herpesvirus genes (61). Orthologous genes are present in cytomegaloviruses infecting nonhuman primates (62), mouse, rat, and guinea pig (63,64). The UL116 ORF from the HCMV TR strain is predicted to encode a 313-amino-acid glycoprotein comprising a signal peptide (amino acid positions 1 to 24) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A major drawback in GPCMV research has largely been overcome by the recent sequencing of the viral genome and the development of infectious bacterial artificial chromosome (BAC) clones of GPCMV (15,(26)(27)(28)(29). Manipulation of an infectious GPCMV BAC has allowed the preliminary study of some viral genes (1,(30)(31)(32)(33)(34)(35)(36).…”
mentioning
confidence: 99%
“…Manipulation of an infectious GPCMV BAC has allowed the preliminary study of some viral genes (1,(30)(31)(32)(33)(34)(35)(36). Analysis of the viral genome (15,29) indicated that GPCMV encodes homologs to the HCMV glycoproteins (gB, gH, gL, gM, gN, and gO) in genes colinear with the HCMV genome (designated GP55, GP75, GP115, GP100, GP73, and GP74, respectively). In HCMV, these six glycoproteins (gB, gH, gL, gM, gN, and gO) are required for fibroblast cell entry, and they form the glycoprotein complexes gCI (gB), gCII (gM/gN), and gcIII (gH/gL/gO) on the viral membrane (37)(38)(39).…”
mentioning
confidence: 99%